KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN EFEKTIVITAS MANAJEMEN SATUAN PENDIDIKAN - Siti Humaeroh; Sholeh Hidayat; Fadlullah Fadlullah (STKIP Pesisir Selatan, 2026)
Objective: Principal leadership plays an important role in improving the effectiveness of educational unit management. Principals function not only as administrators, but also as leaders who are able to direct, coordinate, and empower all school resources to achieve educational goals effectively and efficiently. This study aims to examine the role of principal leadership in improving the effectiveness of educational unit management. The research method used is library research with a descriptive qualitative approach. Data were obtained from various literature sources, including books, scientific journals, research articles, and other references related to educational leadership and school management. The results of the study indicate that adaptive, communicative, and transformational principal leadership has a positive influence on the effectiveness of planning, organizing, implementing, and supervising school management. In addition, effective leadership can improve teacher motivation, create a positive work culture, encourage learning innovation, and strengthen the quality of educational services. Therefore, principal leadership becomes a strategic factor in realizing professional, effective, and quality-oriented educational management.